PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI PT. UTAMA INTI HASIL KIMIA INDUSTRI MEDAN - Sari, Inggrit Puspita; Ningsih, Siska Dwi; Diafatma, Jihan; Hulu, Kristiani Herliani (JURNAL MUTIARA MANAJEMEN, 2024)
Employees are the main wealth in a company, because without their participation, activities cannot be carried out. Each employee will pursue their work a     nd demonstrate behavior in order to gain acceptance or social support and individual status, motivated to be able to meet their personal standards and pursue work that requires special abilities, individuals will further pursue the goals of their company and will then demonstrate good citizenship behavior within the company. Employee behavior outside the duties stated in the job description is called organizational citizenship behavior. One of the factors that influences organizational citizenship behavior is transformational leadership. Transformational leadership is leadership that plays a role in organizational improvement. This research aims to determine the effect of transformational leadership on organizational citizenship behavior in PT employees. Main Core Medan Industrial Chemical Results. The method used in this research is quantitative research. The place of research was carried out at PT. Main Core Medan Industrial Chemical Results. In this study, researchers distributed questionnaires to 73 employees. The research results show that there is an influence of transformational leadership on organizational citizenship behavior in employees at PT. Main Core Results of Medan Industrial Chemistry with a termination coefficient (R2) value of 0.220 showing the influence of transformational leadership of 22% on organizational citizenship behavior with a value of sig. equal to 0.000 ≤ 0.05.